Physics and mathematics of link homology - Seminaire de Mathematiques Superieures Physics and Mathematics of Link Homology (Quebec, Canada 24 June - 5 July, 2013); Gukov, Sergei; Khovanov, Mikhail; Walcher, Johannes (Providence : American Mathematical Society, 2016)
Throughout recent history, the theory of knot invariants has been a fascinating melting pot of ideas and scientific cultures, blending mathematics and physics, geometry, topology and algebra, gauge theory, and quantum gravity. The 2013 Seminaire de Mathematiques Superieures in Montreal presented an opportunity for the next generation of scientists to learn in one place about the various perspectives on knot homology, from the mathematical background to the most recent developments, and provided an access point to the relevant parts of theoretical physics as well. This volume presents a cross-section of topics covered at that summer school and will be a valuable resource for graduate students and researchers wishing to learn about this rapidly growing field.
Chern-Simons theory and knot invariants / Ramadevi Pichai and Vivek Kumar Singh -- Tensor product algebras, Grassmannians and khovanov homology / Ben Webster -- Lectures on knot homology and quantum curves / Sergei Gukov and Ingmar Saberi -- An introduction to knot floer homology / Ciprian Manolescu -- Lectures on knot homology / Satoshi Nawata and Alexei Oblomkov.
Includes bibliographical references.
Keywords: Link theory -- Congresses; Homology theory -- Congresses; Knot theory -- Congresses; Curves -- Congresses